Improvement of Understanding in the Use of E-Taxation System for Tourism Operators in Labuan Bajoe: Peningkatan Pemahaman Penggunaan E-Sistem Perpajakan Pada Pelaku Pariwisata Di Labuan Bajo - Dea Arme Tiara Harahap; Agus Wahyudi; Ni Wayan Noviana Safitri; Ni Made Dwita Ratnaningsih; Ludgardis Deliman (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
Community Service is one of the programs carried out by the Bachelor of Applied Tax Accounting Study Program to carry out the Tri Dharma of Higher Education. Community Service consisting of lecturers and students of the Applied Undergraduate Program in Tax Accounting at the eLbajo Commodus Polytechnic provided material in the field of Introduction to e-system taxation, especially NPWP, and introduction to E-Filling for tourism actors in Labuan Bajo. The method in this activity uses the case study method and is accompanied directly by the Community Service team to tourism actors in resolving tax cases. The importance of community service activities is carried out because there is still a lack of understanding in the field of taxation. It is hoped that after participating in community service activities delivered by the tax accounting study program, tourism actors in Labuan Bajo can pay taxes correctly and regularly in the future